Guest editor - Hadjielias, Elias (My University, 2026)
Journal of Business Research (ABS3): Editor of Special Issue on “Marketing and Consumer Research in Family Business” (due October 31st, 2021) https://www.journals.elsevier.com/journal-of-business-research/call-for-papers/marketing-and-consumer-research-in-family-business